Synthesis and Characterization of Some New 1,3-Oxazepine from"Schiff Bases Contain 1,4-Dihydropyridine - Nariman H. Ibrahim; Muneera Y. Raoof (International Journal of Medical Toxicology and Legal Medicine, 2024)
This study focuses on the synthesis and the development of new Schiff bases and heterocyclic compounds (oxazepine) derived from the starting material 2,6-dimethyl-1,4-dihydropyridine by traditional reflux and green microwave methods."The synthesis of Schiff bases" "using "microwave irradiation" has proven to be significantly easier, faster, reduced solvent, lowering costs and high yield compared to conventional heating methods. Various physical and spectroscopic techniques "FT-IR, 1H-NMR, 13C-NMR and"TLC"were used to"characterize the prepared compounds. Given the documented biological activity of related compounds in the scientific literature, it is expected that these newly synthesized compounds will display similar properties against micro-bacterial.